2015
DOI: 10.1002/ange.201503530
|View full text |Cite
|
Sign up to set email alerts
|

β,β‐Diborylated Subporphyrinato Boron(III) Complexes as Useful Synthetic Precursors

Abstract: Iridium-catalyzed borylation of B-aryl meso-free subporphyrinato boron(III) complexes (hereinafter referred to simply as subporphyrins) with bis(pinacolato)diboron gave 2,13-diborylated subporphyrins regioselectively,w hich served as promising synthetic precursors for 2,13-diarylated subporphyrins and doubly b-to-b 1,3-butadiyne-bridged subporphyrin dimers.2 ,13-Diarylated subporphyrins display perturbed absorption spectra, depending upon the b-aryl substituents.D oubly 1,3-butadiyne-bridged syn and anti subpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…PIH causes the release of anti-angiogenic factors into the mother's circulation, resulting in endothelial injury [2,3]. Previous studies demonstrated that the combined treatment of anti-placental growth factor (PLGF) and vascular endothelial growth factor A (VEGF-A) could reduce ocular hemangiomas growth and choroidal neovascularization [28,29]. The activation of the SOCS/JAK/STAT signaling pathway is an essential pathogenic mechanism leading to endothelial cell dysfunction [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…PIH causes the release of anti-angiogenic factors into the mother's circulation, resulting in endothelial injury [2,3]. Previous studies demonstrated that the combined treatment of anti-placental growth factor (PLGF) and vascular endothelial growth factor A (VEGF-A) could reduce ocular hemangiomas growth and choroidal neovascularization [28,29]. The activation of the SOCS/JAK/STAT signaling pathway is an essential pathogenic mechanism leading to endothelial cell dysfunction [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…[19] Theabsorption spectrum of 15 was clearly different from that of doubly linked dimer 8 but rather similar to that of triply linked dimer 6,s uggesting substantial interaction through the Pt II -linkage. [15] Thee lectrochemical properties of 6, 9,a nd 15 were examined by cyclic voltammetry and differential pulse voltammetry ( Supporting Information, Figures S21-S23). Then arrow optical HOMO-LUMO gap clearly suggests the effective conjugation extending over the whole molecule.T he absorption bands at 315, 403, and 500 nm will be assigned as split Soret-like bands.T hese spectral features are different from those of triply linked porphyrin oligomers 5,w hich generally exhibit two split Soret-like bands.Asimilar trend was also observed in b-to-b doubly butadiyne bridged subporphyrin dimer,w hich has been attributed to the oblique arrangement of the two subporphyrin skeletons.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thed oubly Pt II -bridged subporphyrin dimer 9 was synthesized by reacting b,b-diborylsubporphyrin 10 [15] with Pt(cod)Cl 2 in the presence of CsF and 1,5-cyclooctadiene (COD) in 64 %y ield (Scheme 2). It is worth noting that the syn isomer 9 was asole isolable product, and the corresponding anti isomer was not observed.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] There are three positions available to functionalize subporphyrin, namely, the meso, , and axial positions. [4][5][6][7][8][9][10][11] There are three positions available to functionalize subporphyrin, namely, the meso, , and axial positions.…”
Section: Introductionmentioning
confidence: 99%
“…[7] It was, therefore, natural to expect even stronger electronic interactions to be observed in meso-to-meso butadiyne-bridged subporphyrin dimer 1 [8] and meso-to-meso directly linked subporphyrin dimer as indicated by femtosecond transient absorption anisotropy measurements and theoretical calculations. [10] We developed a method involving a nucleophilic aromatic substitution reaction (S N Ar) to introduce N-, O-, and S-based nucleophiles at the meso position of meso-halosubporphyrins. [9] both of which exhibited largely perturbed and broad Soretlike bands and redshifted Q-like bands.…”
Section: Introductionmentioning
confidence: 99%